PENGEMBANGAN PERMAINAN EDUKATIF LACING CARD UNTUK MENINGKATKAN KETERAMPILAN MOTORIK HALUS ANAK USIA 4 - 5 TAHUN - Siti Nurjannah; Uyu Mu’awwanah; Wulan Fauzia (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2026)
This development research was motivated by obstacles to children's fine motor developmentand the limitations of innovative elearning media in schools. This study aims to developand test the feasibility and effectiveness of the Lacing Cardeducation algame media for early childhood. Using the Research and Development (R & D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), this study involved 15 children aged 4 – 5 years at RA Bina Al Kautsar, West Jakarta. Data were collected through expert validation, performance observation, and interviews. The result sof the validation test showed that the Lacing Card media was categorized as Very Feasible with a score range of 3,80 – 4,00. Empirically, this media has been proven effective in improving children's fine motor skills, as seen from the increase in the average score from 2,30 (Beginning to Develop) at the initial meeting to 3,74 (Developing Very Well) at the final meeting. Significant improvements were recorded in the indicators of independence and accuracy of eye –hand coordination. Teacher responses confirmed that this media is practical and effective as a fine motor stimulation tool. It can be concluded that Lacing Cardis a feasible and optimal learning media for stimulating fine motor development in early childhood.